Intramolecular hydrogen bonds and structural nonrigidity of pyrimidine nucleosides - Mishchuk, Y.R.; Hovorun, D.M. (Биополимеры и клетка, 1998)
Optimal structures and intramolecular web of H-bonds of cytidinc, undine, thymidine, 1heir deoxyribo-analogues and some O5'-, O3'-deutero derivatives were studied by means of MNDOl H semiempirical quantum-chemical method. Effect of the intramolecular H-bonda on the slereochemical structure of nucleosides (particularly, on the stabilization of anti conformation), on the physico-chemical characteristics of nucleoside molecules (heat of formation, dipolc moment, first adiabatic ionization potential and the charge distribution), and on the dynamical characteristics of pyrimidine nucieosides (barriers of the interconvertion, frequencies of the torsional vibrations) was elucidated. The intramolecular 11-bonds in polynudeolides and their influence on the nucleic acid architecture, and nonlinear dynamic properties arc discussed.